Aplikasi Pemesanan Makanan Berbasis Mobile Pada Rumah Makan Lek Nonong - Adi Putra Nugraha; Kodrat Iman Satoto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2014)
The restaurant business that began growing in Semarang in particular areas Tembalang. Various types of food and drink offered by restaurants. Of course, to be able to compete the restaurant needs good management in the effort to obtain optimal benefits. Based on the problems need to develop an Order Food Mobile-Based Application to support the work processes of the restaurant, especially in the booking process and report transactions menu. The mobile application was built using jQuery Mobile programming language and HTML. The use of mobile applications is supported by an application which is running on a desktop computer that was built using the programming language PHP, Javascript and MySQL databases. Modeling applications was built using DFD (Data Flow Diagram). The results of the design Order Food Mobile-Based Application is an application that can be used for the work process and manage reports deals on restaurants, and also an application that can be used to enter the booking menu using mobile devices.